ROLE OF LACTOBACILLUS ACIDOPHILUS IN FERMENTED FEED TO FEED TO IMPROVE THE QUALITY OF BROILER CHICKEN MEAT (PROTEIN, CHOLESTEROL) - Ningrumsari, Ida (Jurnal Pertanian, 2019)
The study aimed to evaluate the administration of L acidophilus in fermented feed to improve the quality of broiler chicken meat (Protein, Cholesterol) which was maintained for 35 days. The material used is 100 chickens that are 1 day old (DOC). The experiment used a laboratory experimental method with a non-factorial Completely Randomized Design with a treatment level consisting of feed type Ro = standard feed, R1 = R0 + Fermented corn husk 10%, R2 = R0 + Fermentation of 20% corn husk, R3 = R1 + L acidophilus 2% and R4 = R2 + L acidophilus 2%. Each treatment was repeated 4 times and each replication contained 5 chickens. The results of analysis of variance showed that administration of    L acidophilus in fermented feed significantly affected the increase in protein (R1) and decreased cholesterol (R3) with an alpha level of 5%. The average protein content R1 = 21.8000 was not significantly different from R4 = 21.5500, while R2 = 21.0500 was significantly different from R3 = 20.6500 and R0 = 20.2000. The lowest average cholesterol level is found in R3 = 64,000 and the highest at R0 = 96,500. While the cholesterol levels R1, R2, R3 and R4 were not significantly different, but were significantly different from R0.